2014
DOI: 10.1117/12.2060801
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on multilayer mirrors: beam profile and coherence properties

Abstract: The main advantage of Bragg reflection from a multilayer mirror as a monochromator for hard X-rays, is the higher photon flux density because of the larger spectral bandpass compared with crystal lattice reflection. The main disadvantage lies in the strong modulations of the reflected beam profile. This is a major issue for micro-imaging applications, where multilayer-based monochromators are frequently employed to deliver high photon flux density. A subject of particular interest is the origin of the beam pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Similar to the previously published study, both mirrors preserve the coherence of the incoming beam in a similar manner: indicated by the identical stripe pattern of the boron fiber. Still, the modulation of the beam profile reflected by the 5 μbar stripe is significantly weaker than for the 1 μbar stripe (peak-to-valley) [15]. …”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…Similar to the previously published study, both mirrors preserve the coherence of the incoming beam in a similar manner: indicated by the identical stripe pattern of the boron fiber. Still, the modulation of the beam profile reflected by the 5 μbar stripe is significantly weaker than for the 1 μbar stripe (peak-to-valley) [15]. …”
Section: Methodsmentioning
confidence: 85%
“…Modified multilayer mirrors were produced in terms of increased interlayer roughness: in a first step a superpolished Si substrate was partially coated with a W/B 4 C stripe (120 bi-layers, 2 nm d-spacing) at the ESRF multilayer deposition facility according to published parameters [13,15]. Next to this stripe (in the middle of the substrate) a second multilayer stripe was deposited, using exactly the same parameters but with the Ar pressure in the coating facility being increased from 1 μbar to 5 μbar (DC magnetron sputtering, power: P(B 4 C) = 500 W, P(W) = 50 W, growth rate R = 0.1 -0.2 nm/s).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The multilayer consists of a system of alternating high and low refractive index materials. In general a striped structure is added to the beamprofile [7,8]: difficult to correct when the monochromator is not stabl. The central bandpass energy can be easily selected by tuning the Bragg angle.…”
Section: Multilayer Monochromatormentioning
confidence: 99%